Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Pemahaman Konsep Matematis Siswa Kelas VII SMPN 2 Ranah Batahan Tahun Pelajaran 2012/2013 - Dola, Era Angga; Anggraini, Villia; Lovia, Lita (STKIP PGRI Sumbar, 2013)
This research of background by students tend to ask her/his friend about her miss understanding in learning than to her/his teacher and it makes a horsy condition. This can be proved from the percentage of students mathematic score in final examination at the first semester. So, this research has purpose to find out the student understanding in mathematical concept at eighth grade ofÂ SMPN 2 Ranah Batahan use cooperative learning strategy type snowball throwing is better than use conventional strategy. The design of this research is experiment. In addition, the population was student at eighth grade of SMPN 2 Ranah Batahan academic year 2012/2013 which consist ofÂ fourth classes and use random technique sampling and was chosen VII.1 as experimental class and VII.2 as control class. The instrument was used is test and essay form. Based on the score of math post-test of two sample classes, the research found that the range value of experiment class is 72,46 and range value of control class is 43,68. The result from hypothesis testing with MINITAB proved P- value = 0,000 smaller than from Î±=0,05. So, it can be concluded that students understanding in mathematical concept by using cooperative learning strategy type snowball throwing is better than using conventional strategy at eighth grade of SMPN 2 Ranah Batahan.